Sosialisasi Perilaku Hidup Bersih dan Sehat (PHBS) dan Dampak Penggunaan Gadget pada Anak - Muhammad Crystandy; Sapriadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Clean and Healthy Living Behavior (PHBS) is an important concept to apply in everyday life. PHBS aims to maintain and improve individual health and prevent the spread of disease. Elementary School (SD) is the initial stage of education where children begin the learning process and develop social skills. The use of gadgets, such as smartphones, tablets and computers, has become an inseparable part of modern life. Gadgets offer access to various applications, games and multimedia content that are interesting for children, replacing healthy physical activities and important social interactions. The method used in this community service is the lecture method in the form of providing education and discussions about Health Promotion Influences Patterns Clean and Healthy Living (PHBS) and the Impact of Using Gadgets on Elementary School Children. Target Elementary School Students Grades 5 and 6 at SD 104294 Pematang Sentrak Village. Time and Place This activity will be held on April 13 2023 at SD 104294 Pematang Sentrak Village, Teluk Mengkudu District, Serdang Bedagai Regency. Implementation of Activities The form of activity carried out is by providing outreach to elementary school students about PHBS and the impact of using gadgets on elementary school children which will have a long-term positive impact on their health and welfare.